Refractory celiac disease type II: An atypical case highlighting limitations of the current classification system. Issue 3 (19th February 2020) - Soderquist, Craig R.; Hsiao, Susan; Mansukhani, Mahesh M.; Alobeid, Bachir; Green, Peter H.; Bhagat, Govind
Abstract: Refractory celiac disease (RCD) is a rare condition associated with high morbidity that develops in individuals with celiac disease. It is known to be biologically heterogeneous, and currently two types are recognized based on immunophenotypic and molecular features, type I (RCD I) and type II (RCD II). Differentiating between RCD I and RCD II is critical, as patients with RCD II have substantially worse outcomes and a high risk of developing enteropathy‐associated T‐cell lymphoma. However, the current RCD classification is limited in scope, and atypical presentations and immunophenotypes are not recognized at present. Herein, we describe a unique case of RCD II with atypical clinical (primarily neurologic manifestations and lack of significant gastrointestinal symptoms), histopathologic (no villous atrophy), immunophenotypic (virtual absence of cytoplasmic CD3 expression), and molecular features (absence of clonal TR rearrangement and identification of pathogenic STAT3 and KMT2D mutations). This case highlights limitations of the current RCD classification system and the utility of next generation sequencing (NGS) studies in the diagnostic workup of RCD. Future algorithms need to recognize extraintestinal manifestations and incorporate atypical histopathologic and immunophenotypic features, as well as results of NGS analysis for RCD II classification.